Potential of Shrimp Shell Extract in Open Fracture Healing - Fauzziah, Prilly Alya; Indriawati, Ratna (Universitas Muhammadiyah Yogyakarta, 2020)
An open fracture is a fracture in which the bone and surrounding tissue are exposed to the external environment. Open fractures are emergency cases in orthopedics. Based on data in 2018, the incidence of fractures reached 5.5% of the total injury cases in Indonesia. The process of blood clotting, platelet infiltration, and polymorphonuclear cells is the first process in bone healing. The conventional methods of bone repair such as autografts, allografts, and xenografts have limitations such as the need for additional surgery, pain, immune reactions, and the risk of transmission. Therefore, this method requires bioactive, biocompatible, and biodegradable molecules. Herbal medicine has become part of the medical field in Indonesia. One of them is a shrimp shell which has active compounds in the form of fatty acids (omega-3 and omega-6), chitosan, minerals, fats, carotenoids (astaxanthin), and vitamins. Chitosan contained in shrimp shell is a derivative of chitin which can be obtained through the deacetylation process. Chitosan has a high affinity for anionic proteins and polysaccharides, is very resistant to heat caused by hydrogen bonds, biodegradable, and flexible which is useful in bone healing. This literature study aims to examine the potential of shrimp shell extract for open fracture healing by tracing electronic database studies, including national and international articles and journals from 2010 to 2020 with a narrative method. The results show that shrimp shell extract that usually just waste can initiate fibroblast, osteoblast, and chondroblast proliferation in the fracture healing process.